Necrotizing cellulitis - Morelli Brum, Raúl; Torterolo, Edgardo; Silva, Celso; Bertullo, Hugo; Viñuela, Enrique; Fischer, Tabaré Mario; Purcher, Héctor (Cirugía del Uruguay, 1977)
Necrotizing Cellulitis has been known under different synonymies since the beginning of this century. A review of bibliography consulted and the study of 15 cases treated by the authors over a twoyear period, indicate that it is a rare disease, a ·wide knowledge of which would be of great interest because of its high morbility and death-rate. The primary and most serious fact is progressive necrosis of subcutaneous tissue, with eventual subsequent necrosis of skin, accompanied by a serious toxic condition caused by especific germs. It affects in general those patients who have had prior diseases. Elective treatment consists of surgical incisions for drainage and debridement. General tract antibiotics are of secondary importance.